2014
DOI: 10.1002/anie.201410806
|View full text |Cite
|
Sign up to set email alerts
|

Type II Intramolecular [5+2] Cycloaddition: Facile Synthesis of Highly Functionalized Bridged Ring Systems

Abstract: A type II intramolecular oxidopyrylium-mediated [5+2] cycloaddition reaction allows the efficient and diastereoselective formation of various highly functionalized and synthetically challenging bridged seven-membered ring systems (such as bicyclo[4.4.1]undecane, bicyclo[4.3.1]decane, bicyclo[5.4.1]dodecane, and bicyclo[6.4.1]]tridecane). This simple, thermal, direct transformation has a broad substrate scope and is high yielding, with high functional-group tolerance and unique endo selectivity. The highly stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…Several elegant approaches to the construction of the cyclocitrinol core framework have been reported including Schmalz’s SmI 2 -mediated cyclopropane fragmentation, Leighton’s tandem ring-contracting Ireland–Claisen/Cope rearrangement sequence, and Li’s type II intramolecular oxidopyrylium-mediated [5 + 2] cycloaddition (Scheme ). Li and co-workers recently reported the first total synthesis of cyclocitrinol, starting from a vitamin D 2 degradation product, highlighting the synthetic utility of intramolecular cycloadditions for the synthesis of complex natural products …”
Section: Resultsmentioning
confidence: 99%
“…Several elegant approaches to the construction of the cyclocitrinol core framework have been reported including Schmalz’s SmI 2 -mediated cyclopropane fragmentation, Leighton’s tandem ring-contracting Ireland–Claisen/Cope rearrangement sequence, and Li’s type II intramolecular oxidopyrylium-mediated [5 + 2] cycloaddition (Scheme ). Li and co-workers recently reported the first total synthesis of cyclocitrinol, starting from a vitamin D 2 degradation product, highlighting the synthetic utility of intramolecular cycloadditions for the synthesis of complex natural products …”
Section: Resultsmentioning
confidence: 99%
“…Most previous studies have focused on intramolecular oxidopyrylium‐alkene cycloaddition with the alkene 2π components tethered to C2 or C6 position, that is, type I oxidopyrylium–alkene cycloaddition . In 2015, Li's group demonstrated that type II [5+2] cycloaddition is feasible by tethering the alkene to the C5 position of an oxidopyrylium ylide, which leads to various highly functionalized bridged seven‐membered carbocycles . This reaction was then applied to the construction of the carbon core of eurifoloid A and the total synthesis of isocyclocitrinol .…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, there have been no reports of type II IMDA reactions being used to make bicyclo[5.2.2], bicyclo [4.2.2], and bicyclo[3.2.2] ring systems. In addition, other type II intramolecular cycloadditions 22 , 23 (including innovative Davies-[4+3] 24 , remarkable Wender-[4+4] 25 , and our [5+2] 26 , 27 ) are unknown for the synthesis of bicyclo[m.n.2] ring systems. Currently, few intramolecular cycloaddition reactions are available for the direct and efficient synthesis of various bicyclo[m.n.2] ring systems.…”
Section: Introductionmentioning
confidence: 99%